Preparation of 3DOM ZrTiO4 Support, WxCeMnOδ/3DOM ZrTiO4 Catalysts, and Their Catalytic Performance for the Simultaneous Removal of Soot and NOx - Wang, Ruidan; Zhong, Chengming; Li, Dong; Yu, Xuehua; Zhao, Zhen; Sojka, Zbigniew; Kotarba, Andrzej; Wei, Yuechang; Liu, Jian (Frontiers in Chemistry, 2022)
As an efficient and durable engine, a diesel engine has a broad application. However, soot particles (PM) and nitrogen oxides (NOx) coming from diesel engines are the main causes of air pollution, so it is necessary to design and prepare an effective catalyst for the simultaneous elimination of PM and NOx. In this work, a novel 3DOM ZrTiO4 support and a series of WxCeMnOδ/3DOM ZrTiO4 catalysts (where x indicates the wt% of W) were designed and fabricated by the colloidal crystal template technique. Among the as-prepared catalysts, the W1CeMnOδ/3DOM ZrTiO4 catalyst exhibits the highest NO conversion rate (52%) at the temperature of maximum CO2 concentration (474°C) and achieves 90% NO conversion in the temperature range of 250–396°C. The excellent catalytic performance is associated with the macroporous structure, abundant oxygen vacancies, sufficient acid sites, and the synergistic effect among the active components. The possible reaction mechanisms of WxCeMnOδ/3DOM ZrTiO4 catalysts were also discussed based on the characterization results.